Profile of nutritional status, energy availability, haemoglobin levels and bone density in santriwati (Islamic female student) with chronic energy deficiency risk - Fillah Fithra Dieny; A Fahmy Arif Tsani; Umu Faradilla; Ayu Rahadiyanti (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2021)
Background: Santriwati (Islamic female student), women of reproductive age, were susceptible to experienced Chronic Energi Deficiency (CED). CED reflects the low energy availability of someone who can risk reducing bone density. Objectives: This study aimed to analyze the differences in body mass index, body fat percentage, hemoglobin levels, energy availability, and bone mineral density of female students who experienced CED risk and not experienced CED risk.Materials and Methods: The research design was a cross-sectional study, with 101 female students as subjects who were selected by random sampling. The research was conducted from February to March 2019 at the Kyai Galang Sewu Islamic Boarding School, Semarang. CED risk data was taken using the upper arm circumference measurement. Percent body fat and BMI data were taken using BIA. Energy availability data is obtained from the difference between energy intake (energy intake) and energy output (energy expenditure through physical activity) divided by Fat-Free Mass (FFM). Energy intake data was taken using the SQ-FFQ questionnaire, and energy expenditure was calculated using the 24-hour activity record form. Anemia data were collected using strip hemoglobin measurements. Bone density data were taken using the Osteosys Sonost 3000 densitometer. Bivariate analysis used the Independent T-Test.Results: A total of 57.2% of subjects experienced anemia. Subjects who had underweight nutritional status were 20.8%. Santriwati experienced osteopenia as much as 13.9%. There was no difference in bone density and hemoglobin levels between female students who were at risk of CED and not CED risk (p> 0.05), but there were differences in energy availability, body fat percentage, BMI between those at risk of CED and not CED risk (p <0.05)Conclusion: subjects at risk of CED (Lila <23.5 cm) had lower energy availability, body fat, and BMI than subjects who were not at risk of CED.